2001
DOI: 10.1136/sti.77.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and vaginal douching in a population of female sex workers in Nairobi, Kenya

Abstract: Objective: To assess the association between vaginal douching and sexually transmitted infections (STI) among a group of female sex workers (FSWs) in Nairobi, Kenya. Methods: This study was part of a randomised, placebo controlled trial of monthly prophylaxis with 1 g of azithromycin to prevent STIs and HIV infection in a cohort of Nairobi FSWs. Consenting women were administered a questionnaire and screened for STIs. Results: The seroprevalence of HIV-1 among 543 FSWs screened was 30%. HIV infection was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
4
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 21 publications
8
78
4
10
Order By: Relevance
“…The reason for higher BV in HIV-positive women in the African population is not known, but the correlation between HIV serostatus and lifestyle practice such as vaginal douching and no use of condoms could explain this increased prevalence of BV [13,14,15]. However, this association may be influenced by the level of education and other socio-economic and behavioural factors which must be taken into consideration.…”
Section: Discussionmentioning
confidence: 88%
“…The reason for higher BV in HIV-positive women in the African population is not known, but the correlation between HIV serostatus and lifestyle practice such as vaginal douching and no use of condoms could explain this increased prevalence of BV [13,14,15]. However, this association may be influenced by the level of education and other socio-economic and behavioural factors which must be taken into consideration.…”
Section: Discussionmentioning
confidence: 88%
“…One study conducted in Rwanda and Kenya showed that~5% of FSWs reported ever practicing anal sex, 2 but many other studies in Kenya indicate higher prevalence levels of anal sex among FSWs ranging between 14% and 40%. [19][20][21][22][23] A study conducted in South Africa suggests that more than 40% of the FSWs soliciting at truck stops had engaged in anal sex. 24 Other research in South Africa suggests that FSWs, on average, engage in five anal sex acts per week.…”
Section: Introductionmentioning
confidence: 99%
“…is a common practice among women around the world. 7,8 There is some evidence that frequent vaginal douching may increase a woman's susceptibility to sexually transmitted agents through modification of the vaginal flora. A meta-analysis reviewing 13 studies revealed that frequent douching appears to be highly associated with pelvic inflammatory disease (PID) and modestly associated with ectopic pregnancy and cervical cancer.…”
mentioning
confidence: 99%